Getting the JNPS Indexed - Editor, The (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3126/jnps.v29i1.1591 J. Nepal Paediatr. Soc. Vol.29(1) p.1-2